3D printing of porcelain by layerwise slurry deposition. Issue 9 (August 2018) - Lima, Pedro; Zocca, Andrea; Acchar, Wilson; Günster, Jens
Abstract: The Layerwise Slurry Deposition is a technology for the deposition of highly packed powder layers. A powder bed is achieved by depositing and drying layers of a ceramic suspension by means of a doctor blade. This deposition technique was combined with the binder jetting technology to develop a novel Additive Manufacturing technology, named LSD-print. The LSD-print was applied to a porcelain ceramic. It is shown that it was possible to produce parts with high definition, good surface finish and at the same time having physical and mechanical properties close to those of traditionally processed porcelain, e.g. by slip casting. This technology shows high future potential for being integrated alongside traditional production of porcelain, as it is easily scalable to large areas while maintaining a good definition. Both the Layerwise Slurry Deposition method and the binder jetting technologies are readily scalable to areas as large as >1 m 2 .